1999
DOI: 10.1007/s007050050582
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of an early/late bi-directional promoter of the capripoxvirus, lumpy skin disease virus

Abstract: Identification and characterisation of an early/late bi-directional promoter element of lumpy skin disease virus (LSDV) is described. The 56 bp element shows substantial structural similarities with other poxvirus promoters, providing further evidence that transcriptional elements are conserved within the Poxviridae. The relative strengths of the LSDV early and late promoters were compared to the vaccinia virus (VV) P7.5K and P11K promoters in transient expression assays. These transient assays also verified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Current molecular data on the LSDV genome consists of restriction endonuclease analysis, cross-hybridization studies, and limited transcriptional and DNA sequence analysis (5,19,20,26,27,33). Given the economic significance of LSD, its potential for spread into nonenzootic regions, and the interest in developing more effective LSDV-based vaccines and expression vectors, we have sequenced and analyzed the genome of a pathogenic LSDV.…”
mentioning
confidence: 99%
“…Current molecular data on the LSDV genome consists of restriction endonuclease analysis, cross-hybridization studies, and limited transcriptional and DNA sequence analysis (5,19,20,26,27,33). Given the economic significance of LSD, its potential for spread into nonenzootic regions, and the interest in developing more effective LSDV-based vaccines and expression vectors, we have sequenced and analyzed the genome of a pathogenic LSDV.…”
mentioning
confidence: 99%
“…Previously, the use of GTPV as a vaccine vector has been reported in China and abroad, and numerous ruminant mammal protective antigens have been expressed in the GTPV vaccine vector expression system, which have demonstrated promising results (17,18). The present study selected VVI1L promoter-expressed exogenous genes as VVI1L is a strong promoter, as its activity is 10-fold greater than that of VVP7.5 (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…While sequencing the genome, a 42 nucleotide (nt) sequence was identified that seemed unusually well conserved; unusual in both its length and the fact that it was almost perfectly conserved between members of four different poxvirus genera. Although subsequent experiments on the CSE ultimately led to its classification as a promoter element in poxviruses [10], the CSE remains unusual because it is remarkably well conserved for a promoter, it is longer than the average poxvirus promoter (which is normally in the range of ∼30 nts) [11], and it actually contains both early and late promoter elements that are believed to act on an early/late gene [11,12]. The presence of both early and late promoter elements, as well as the very high conservation of the CSE, makes it more complex than other characterized promoters [10,1314].…”
Section: Introductionmentioning
confidence: 99%